Frequency of Different Types of Diagnostic Errors in Patients with Central Nervous System Infections: A Cross-Sectional Observational Study - HamidReza Naderi; Fereshte Sheybani; Omid Khosravi; Mehdi Jabbari Nooghabi (Neurology Research International)
Objectives. To assess the frequency of different types of diagnostic errors in patients with central nervous system (CNS) infection from the onset of symptoms to admission to the hospital, where the correct diagnosis was made. Methods. A cross-sectional observational design was used, and the information was collected by interviewing patients and/or their knowledgeable relatives as well as reviewing the accompanying medical record documents and hospital records. Results. Of 169 adult patients with CNS infection, 129 (76.33%) were subject to diagnostic errors. Failure in ordering tests and hypothesis generation were the most common types of diagnostic errors that accounted for more than 70% of errors. Several contributing factors that were associated with incorrect diagnostic hypotheses included failure in taking a patient’s comprehensive history such as detecting relevant epidemiological clues, conducting a full clinical examination, and interpreting diagnostic evidence. The relationship between poor clinical outcome and longer delay from the onset of illness to diagnosis, inappropriate empirical antibiotic therapy, and lower level of consciousness on admission were found to be statistically significant. Conclusions. Although diagnosis and management of CNS infection in some patients are straightforward, clinical decision making in facing patients with complex scenarios often requires clinical reasoning instead of relying only on intuitive diagnosis. Justification in requesting diagnostic measures and interpretation of their results based on clinical findings and patient information could be a critical factor in preventing a substantial number of diagnostic errors in patients with CNS infection.